2020
DOI: 10.1038/s41467-019-13901-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinically accurate diagnosis of Alzheimer’s disease via multiplexed sensing of core biomarkers in human plasma

Abstract: Alzheimer's disease (AD) is the most prevalent neurodegenerative disorder, affecting one in ten people aged over 65 years. Despite the severity of the disease, early diagnosis of AD is still challenging due to the low accuracy or high cost of neuropsychological tests and neuroimaging. Here we report clinically accurate and ultrasensitive detection of multiple AD core biomarkers (t-tau, p-tau 181 , Aβ 42 , and Aβ 40) in human plasma using densely aligned carbon nanotubes (CNTs). The closely packed and unidirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(122 citation statements)
references
References 41 publications
0
118
1
3
Order By: Relevance
“…The black bars indicate minor transcripts that encode proteins in a different reading frame from the overlapping major mRNA. Reproduced with permission from ( Kim et al, 2020c ). (E) Phylogenetic tree of SARS-CoV-2 and other pathogenic human CoVs, including HCoV-229E, HCoV-HKU1, HCoV-NL63 HCoV-OC43, and MERS-CoV.…”
Section: Overview Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…The black bars indicate minor transcripts that encode proteins in a different reading frame from the overlapping major mRNA. Reproduced with permission from ( Kim et al, 2020c ). (E) Phylogenetic tree of SARS-CoV-2 and other pathogenic human CoVs, including HCoV-229E, HCoV-HKU1, HCoV-NL63 HCoV-OC43, and MERS-CoV.…”
Section: Overview Of Sars-cov-2mentioning
confidence: 99%
“…The high-sensitivity of G-FET was also recently used to detect SARS-CoV-2 virus particles in human NS specimens ( Seo et al, 2020 ). Moreover, carbon nanotube-based FET sensors have shown great promise for the highly sensitive detection of virus antigens, antibodies, nucleic acids, and virus particles in clinical samples ( Choi et al, 2017 ; Kim et al, 2020b ; Mandal et al, 2012 ; Oh et al, 2013 ; Ramnani et al, 2013 ; Son et al, 2016 ).…”
Section: Potential Biosensors For Point-of-care Sars-cov-2 Detectionmentioning
confidence: 99%
“…Perez-Grijalba et al showed that a decreased plasma Aβ42/Aβ40 ratio alone can accurately predict positivity and detect early stages of AD [76,77]. Using a multiplex sensor array, Kim et al showed that a lower Aβ42/Aβ40 ratio and a higher plasma t-tau/Aβ42 and p-tau 181/Aβ42 ratios successfully discriminated AD patients from healthy controls [78]. In addition to plasma Aβ levels, Nabers et al showed that a change in the secondary structure of Aβ in human blood plasma can be used as a blood amyloid indicator for prodromal AD.…”
Section: Blood Aβ Markersmentioning
confidence: 99%
“…Consistently decreased in CSF, also decreased in blood [20][21][22][23][24][25][26][27][28][29][74][75][76][77][78]…”
Section: Aβ42mentioning
confidence: 99%
“…5 . This was used to measure levels of AD biomarkers using fluorescence and resistance measurement techniques, showing LOD values of 2.45, 2.72, 2.20, and 2.13 fM/mL for t-tau, p-tau181, Aβ42, and Aβ40, respectively [ 146 ]. An electrochemical immunoassay has been developed by Diba et al from sandwich immunoassay fabricated with an antibody coated on a monolayer obtained by mixing 3-mercaptopropionic acid (MPA) and thiol modified polyethylene glycol (PEG-SH) localized on AuNPs over the screen printed carbon electrode (SPCE).…”
Section: Introductionmentioning
confidence: 99%